Hafif Düzeyde Zihinsel Öğrenme Güçlüğü Olan Bir Öğrencinin Okuma Ve Anlama Becerilerini Geliştirmeye Yönelik Nitel Bir Çalışma - KURTDEDE FİDAN, Nuray; AKYOL, Hayati (My University, 2011)
Bu araştırma, hafif düzeyde zihinsel öğrenme güçlüğü olan, Afyonkarahisar İli Merkez H.A.Y. İlköğretim Okulu dördüncü sınıf öğrencisi on bir yasındaki bir kız öğrencinin okuma becerileriyle ilgili yetersizliklerinin tespiti ve giderilmesine yönelik olarak gerçekleştirilmiştir. Öğrencinin uygulama öncesi okuma beceri düzeyini belirlemek için kişisel değerlendirme formları ve Yanlış Analizi Envanteri kullanılmıştır. Okuma ve okuduğunu anlama düzeyini belirlemek için öğrenciye üç alt sınıf düzeyine ait okuma metinleri verilmiştir. Bu ön uygulama sonucunda öğrencinin Yanlış Analizi Envanterine göre okuma düzeyi bakımından endişe düzeyinde olduğu tespit edilmiştir. Öğrencinin okuma becerisini geliştirmek amacıyla 2006–2007 öğretim yılının bahar dönemi boyunca çeşitli çalışmalar gerçekleştirilmiştir. Bu çalışmalar sonucunda S.U.’ nun okuma ve anlama düzeyi “Endişe Düzeyinden” “Serbest Düzeye” yükselmiş ve okuma alanındaki yetersizliklerinde iyileşmeler görülmüştür.
The Qualitative Research on the Improvements of the Reading and Comprehension Skills of a Student with Mildly Mental Retardation
This study has been designed to determine and deal with the inadequacy of reading and comprehension skills of a 11 year-old mildly mentally retarded girl student studied at 4th grade at one of the H.A.Y. Primary Schools in Afyonkarahisar city. As a pre-assessment, personal evaluation forms and Reading Miscue Inventory were used in order to determine the baseline level of reading ability. Due to find out the specific level of reading and comprehension ability, 1st grade (3 grades backward) of reading materials were given to this student. As a result of this pre-assessment, it was revealed that this student can be categorized as “anxious level” on reading ability on the basis of Reading Miscue Analysis.. Throughout 2006-2007 spring education period, several kinds of studying materials were applied to the student. As a consequent of these applications the reading and understanding level of S. arised the “Free Level” from the “Anxiety Level” and the improvements were seen in reading disabilities.
Keywords: Reading and comprehension, reading difficulty, repeated measures